METAPHORICAL AND PERSUASIVE LANGUAGE IN THE ADVERTISEMENTS OF THE TEEN VOGUE MAGAZINE - Erie Estie Wahyuningbyas (INFERENCE: Journal of English Language Teaching, 2018)
The challenge of making print ads is to choose the best marketing approach for the product or brand that is advertised. Another imaginative approach that can be used to render print ads in magazines is a metaphor. Using descriptive qualitative research using the theory of conceptual metaphor by Lakoff-Johnson as well as Keraf, this research searches for: a) what are some types of metaphorical and persuasive classifications that often appear? and b) what the relationship between metaphorical and persuasive language styles is? Based on data analysis, six metaphorical data and 15 persuasive data were found from 27 data from the Teen Vogue magazine, May 2012 edition. The results also showed that there were two structural metaphors, four ontology metaphors, and one orientation metaphor. The type of metaphor that often appears is the ontology metaphor. While the type of classification of persuasive methods that appear shows there are eight methods of suggestion, three methods of rationalization, two methods of compensation, one method of replacement, one method of projection.Key Words: semantic; advertisement; meaning; metaphor; persuasive